Looking for the European Voter: Split-Ticket Voting in the Belgian Regional and European Elections of 2009 and 2014 - Kelbel, Camille (2016)
While European elections are often seen as remote from EU issues, considerations specifically linked to the EU came to the forefront in the wake of the 2014 European elections: the economic and financial crisis, the new process of designation of the European Commission President, and the alleged increase of Eurosceptic votes. This increased salience of political debates about the EU asks for a reconsideration of the ‘second-order nature’ of European elections. In this context, as in 2009, the Belgian electorate voted for the regional and European levels on the very same day. Belgian voters were thus offered the opportunity to split their ticket between both levels. This allows comparing the occurrence and determinants of these ‘immediate switching’ behaviours in 2014 with those of the presumably less politicized EP elections in 2009. We do that by employing the 2009 and 2014 PartiRep Election Study data. On the one hand, the article shows that split-ticket voting cannot be explained by economic voting, European identity, and attitudes towards integration in 2014. On the other hand, the unique configuration of the Belgian elections enables us to observe that the introduction of Spitzenkandidaten did enhance split-ticket voting for voters who could directly vote for this candidate (in Flanders), while this did not increase split-ticket voting among voters who could only indirectly support the candidate (in Wallonia).